An analytical study of the pricing of Islamic home financing and conventional home loan in Malaysia - Othman bin Abdullah (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2012)
A place called home is a basic need in human live. For most people, buying a house is a significant investment as house prices have been increasing steadily. Due to the high price, most Malaysians finance their house purchases with bank loan or financing. At the moment, Malaysians may opt for conventional home loan or Islamic financing for reasons suitable for them. For Islamic financing, the products available are BBA Home Financing or MM Home Financing. Statistical evidence shows that the amounts of conventional loans and Islamic fmancings for the purpose of house purchases have also been increasing every year. Despite stiff competitions by financial institutions in designing attractive home loans and financing packages to meet customers' demands, there are perceptions that Islamic home financing in Malaysia is more expensive than conventional home loan. However, claims have also been made that both conventional home loan and Islamic home financing products are competitive in terms of both product structure and pricing. This research paper attempts to analytically study the pricing of Islamic home financing versus conventional home loan to examine the competitiveness of the pricing of conventional home loan and Islamic home financing. Specifically, this research will identify the components of loan and financing prices, the formula used in calculating the various price components and the factors that affect the price calculations. This research will also gather available pricing related data and finally make comparisons of the various pricing components of conventional home loan and Islamic home financing. The finding of this research shows that the pricing formula for conventional loan and Islamic financing are the same. If all factors affecting pricing calculation are the same, the price of a conventional home loan and Islamic will be exactly the same. What makes a loan or a financing more expensive than the other is the product feature and other terms and conditions imposed by the loan or financing providers. There was some truth that product feature wise, Islamic BBA home financing appeared to be more expensive in the past. Now that Islamic banking products have evolved, the pricing of floating rates BBA and MM fmancing have become very competitive with conventional home loan products.